Technology and Resilience - Cirera, Xavier (The World Bank, 2022)
This paper estimates the impact of technology sophistication pre-COVID-19 on the performance of firms during the early stages of the pandemic. It exploits a unique data set covering firms from Brazil, Senegal, and Vietnam, using a treatment effect mediation framework to decompose the results into direct and indirect effects. Increasing pre-pandemic technology sophistication by one standard deviation is associated with 3.8 percentage points higher sales. Both effects are positive, but the direct effect is about five times larger than the indirect effect. The total effect on sales is markedly nonlinear with significantly smaller estimates of the reduction in sales for firms with more sophisticated pre-pandemic technology. The results are robust to different measures of digital responses and matching estimators
Keywords: Business Cycles and Stabilization Policies; Common Carriers Industry; Digital Technology; Effects Of Technology; Food and Beverage Industry; General Manufacturing; Industry; Innovation and Entrepreneurship; Macroeconomics and Economic Growth; Nationally Representative Survey; Supply Chain Management System; Technology Index; Urban Transport